Cardiovascular manifestations in the Ehlers-Danlos syndrome hypermobile type - Villarroel-Ábrego, Hugo (2020)
Introduction In the hypermobile Ehlers-Danlos syndrome (EDSht) there is an important frequency of cardiovascular symptoms. Studies have been conducted in patients diagnosed with Brighton criteria. The objective of this research was to determine the frequency of echocardiographic symptoms and abnormalities in the unselected adult population, diagnosed with EDSht, in a cardiology office, with the criteria of the International Classification of Ehlers-Danlos syndromes, published in 2017. Methods The descriptive study in patients diagnosed with EDSht was employed, older than 12 years, attended in an outpatient clinic of cardiology of San Salvador, El Salvador, between 2012 and 2019. Clinical history, physical examination, anthropometry, the Beighton score was employed, 10-minute postural test and echocardiography (ECHO) findings were recorded. Results The EDSht was diagnosed in 57 patients, 9: 1 ratio between genders, female predominance; average age was 32.3 + 12.8 years. ECHO was performed in 93% of subjects. The most reported symptom was palpitations (75.4%), but cardiovascular symptoms (chest pain, dyspnea, palpitations, presyncope or syncope) were found in 91.2% of cases. The Dysautonomia (POTS and/or hypotension/orthostatic intolerance) was present in 53.6% of patients. Mitral prolapse had a frequency of 13.2%, valvular myxomatous changes in 17% of cases. An abnormal aortic Z score was infrequent (4 of 53 patients, 7.5%). The echocardiogram showed at least one abnormality in the 26.4% of subjects. Conclusion In the EDSht, a high frequency of cardiac symptoms, dysautonomia and abnormal ECHO is recorded. The search for cardiovascular abnormalities when diagnosing EDSht is justified; reciprocally, in young patients with cardiovascular manifestations it is convenient to consider the diagnosis of EDSht.